2019
DOI: 10.3390/md17110615
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation with the Red Seaweed Porphyra umbilicalis Protects against DNA Damage and Pre-Malignant Dysplastic Skin Lesions in HPV-Transgenic Mice

Abstract: Some diet profiles are associated with the risk of developing cancer; however, some nutrients show protective effects. Porphyra umbilicalis is widely consumed, having a balanced nutritional profile; however, its potential for cancer chemoprevention still needs comprehensive studies. In this study, we incorporated P. umbilicalis into the diet of mice transgenic for the human papillomavirus type 16 (HPV16), which spontaneously develop pre-malignant and malignant lesions, and determined whether this seaweed was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Porphyra umbilicalis incorporated diets in human papillomavirus Type 16 (HPV16), infected transgenic mice are tested for checking its malignancy development (multistep carcinogenesis) induced by HPV. From the study, the P. umbilicalis significantly blocked the development of pre-malignant skin lesions and indicate its antigenotoxic activity against HPV-induced DNA damage [56].…”
Section: Porphyranmentioning
confidence: 79%
“…Porphyra umbilicalis incorporated diets in human papillomavirus Type 16 (HPV16), infected transgenic mice are tested for checking its malignancy development (multistep carcinogenesis) induced by HPV. From the study, the P. umbilicalis significantly blocked the development of pre-malignant skin lesions and indicate its antigenotoxic activity against HPV-induced DNA damage [56].…”
Section: Porphyranmentioning
confidence: 79%
“…In the literature, there is a lack of studies regarding the effects of seaweeds bioactive molecules on premalignant dysplastic lesions. We found only one study conducted by Santos et al [ 83 ], which reported the effects of Porphyra umbilicalis on HPV-transgenic mice with pre-malignant dysplastic skin lesions. This seaweed was incorporated into the diet of HPV 16-infected mice, which have developed pre-malignant and malignant lesions, in order to determine whether this product can block the development of these lesions.…”
Section: Resultsmentioning
confidence: 97%
“…This seaweed was incorporated into the diet of HPV 16-infected mice, which have developed pre-malignant and malignant lesions, in order to determine whether this product can block the development of these lesions. After the follow-up period, the investigators reported that Porphyra umbilicalis blocked the development of pre-malignant lesions and exerted antigenotoxic activity against HPV-induced DNA damage [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…New drugs are being developed from secondary metabolites to discover less toxic and more effective compounds compared to traditional cancer therapies [13]. Some natural products have also become important nutraceuticals with cancer chemopreventive properties [14,15].…”
Section: Introductionmentioning
confidence: 99%